Effect of intraoperative noise isolation on postoperative nausea and vomiting in patients undergoing gynecological laparoscopic surgery: protocol for a randomized controlled trial - Chong Fu; Fan Xia; Zihan Yan; Han-bing Xu; Wei-ming Zhao; Yi-shan Lei; Chang Xu; Wen-wen Huo; Duo-duo Tao; Juan Wang; Xi-sheng Shan; Ke Peng; et al. (BMC Anesthesiology)
Abstract Background Postoperative nausea and vomiting (PONV) are common complications following general anesthesia, particularly in gynecological laparoscopic surgeries. This study aims to evaluate the effect of intraoperative noise isolation on PONV incidence. Method This single-center, prospective, randomized controlled trial will enroll 192 adult patients undergoing laparoscopic gynecological surgery. Patients will be randomly assigned in a 1:1 ratio and stratified by age into either the control group (Group C), without noise-cancelling headphones, or a noise reduction group (Group NR), using noise-cancelling headphones from anesthesia induction until the end of surgery. All patients will receive intraoperative dexamethasone and ondansetron prophylaxis. The primary outcome is the incidence of PONV within 48 h post-surgery. Secondary outcomes include PONV severity at 24 and 48 h, antiemetic use, pain scores, need for rescue analgesia, Quality of Recovery-15 (QoR-15) scores, Richards-Campbell Sleep Questionnaire (RCSQ) scores, hemodynamic interventions, extubation time, length of stay in PACU and hospital, adverse events (hypertension, hypotension, bradycardia, tachycardia, desaturation after extubation, postoperative shivering, emergence agitation, allergic reactions, severe arrhythmias arrhythmia, cardiac arrest, hypothermia), patient satisfaction, and postoperative complications based on the Postoperative Morbidity Survey (POMS). Analyses will be conducted using modified intention-to-treat (mITT) and per-protocol (PP) populations. Discussion We hypothesize that intraoperative use of noise-cancelling headphones will reduce PONV incidence in patients undergoing gynecological laparoscopic surgery. The findings could enhance postoperative care protocols for thoracoscopic gynecological procedures. Trial registration Chinese Clinical Trial Registry (ChiCTR2400087460).